Intuitive eating buffers the link between internalized weight stigma and body mass index in stressed adults. (1st February 2022) - Braun, Tosca D.; Unick, Jessica L.; Abrantes, Ana M.; Dalrymple, Kristy; Conboy, Lisa A.; Schifano, Elizabeth; Park, Crystal L.; Lazar, Sara W.
Abstract: Internalized weight stigma (IWS) is independently associated with less intuitive eating (i.e., eating based on endogenous hunger/satiety cues) and higher Body Mass Index (BMI), and intuitive eating training is commonly conceptualized as protective against the effects of IWS on poor behavioral health. The 3-way relationship between IWS, intuitive eating, and BMI has yet to be examined, and it is unclear whether the link between IWS and BMI is buffered by high intuitive eating. This secondary preliminary analysis examined baseline data of stressed adults with poor diet (N = 75, 70% female, 64.1% White, 42.7% with overweight/obesity) in a parent clinical trial that tested the effects of yoga on diet and stress. Validated self-report surveys of IWS and intuitive eating were analyzed with objectively-assessed BMI. Moderated regression analyses using the SPSS PROCESS macro tested whether intuitive eating moderated the IWS-BMI link. The analysis revealed IWS was positively associated with BMI except among people with high intuitive eating. Results extend observational findings linking intuitive eating to lower BMI, and offer preliminary support for the hypothesis that this link may hold even among those with greater IWS. It's possible that individuals with lower BMI and greater IWS may gravitate more towards intuitive eating than those with greater BMI, and/or intuitive eating may be an important target for ameliorating the adverse association of IWS with behavioral and physical health indicators linked to BMI. Continued work is warranted in larger, more generalizable samples using causal and prospective designs.